Mobile E-Portfolios on Google Sites: A Tool for Enhancing Project-Based Learning - Tran, Thi Ngoc Anh; Nguyen Ngoc, Truong (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Project-based learning is a student-centered approach to learning that emphasizes hands-on experiences, collaboration, and real-world problem-solving. The process of evaluating students’ learning outcomes in a learning project, however, faces numerous challenges. This study investigates the potential of mobile e-portfolios on the Google Sites platform as a means of enhancing project-based learning in the field of physics education. The study utilized a quasi-experimental design with two groups: an experimental group and a control group. The data collected from the pre-test and post-test were analyzed using a t-test to determine the significance of the difference in the mean scores between the experimental group and the control group. The questionnaire data were analyzed using descriptive statistics to identify patterns and trends in student feedback. The results show that the use of mobile e-portfolios on the Google Sites platform significantly enhanced student interest and learning outcomes. After the pedagogical experiment, the experimental group’s test scores (7.92) were higher than the control group’s (5.22). According to the findings of the survey questionnaire given to the experimental group, the majority of students indicated that using mobile e-portfolios boosted their involvement and motivation to learning, as well as their ability to plan and present their project work. In conclusion, the findings of this study suggest that mobile e-portfolios on Google Sites can be an effective tool for enhancing project-based learning.